Knowledge, Attitude and Use of Evidence Based Nursing Practice among Nurses Working at Tertiary Level Cancer Hospital: “Where Do we Stand?” - Sharma, Sarojini; Thapa, Usha; Koirala, Sushila; Upadhaya, Hari Prasad (Nepalese Journal of Cancer, 2025)
Background: Evidence-based practice (EBP) in oncology nursing is a clinical decision-making approach in nursing care that improves quality care and outcomes in health care but is not yet standard in clinical settings.Objectives: The purpose of this study was to determine EBP knowledge, attitude and practice of oncology nurses.Methods: Cross sectional study used the self-administered Evidence-Based Practice Questionnaire (EBPQ) developed by Upton and Upton in the United Kingdom. Simple random sampling technique was used toselect the sample. The sample size was 139 nurses working in tertiary level cancer hospital Chitwan.Results: Out of 139 respondents, all of them were female. Mean age of the respondents was 31.9712 sd±7.30390 where minimum age found to be 20 years and maximum was 55 years. In regards to marital status 74.1% of the respondents were married, remaining 24.9% were unmarried. In terms of education more than half (56.8%) of respondents had Bachelor in Nursing Science (BNS) degree, 24.5% had Bachelor of Science in Nursing degree, 11.5% had proficiency certificate level degree and remaining 7.2% had master degree. The mean year of experience was = 8 years sd±6.77809 with minimum 6 month, Maximum=28 years. In terms of designation, most of the respondents (76.3%) were working in staff nurse post. In three sub scale of evidence based practice, Good level of knowledge 41.7%, positive attitude 40.3%and good practice 41.7% was found to be on less than fifty percent of the respondents. Poor level of knowledge, negative attitude and poor practice was found among 34.5%, 30.9% and 34.5% respectively. Fair level of knowledge, neutral attitude and fair practice was reported by 23.5%, 28.8% %23.7% respectively. Findings shows that knowledge, attitude and practice is significantly associated with level of education of the respondents (p=.000) at 0.05 level of significance. Findings further shows there exist significant correlation between knowledge attitude and practice among respondents on evidence based nursing practice. Respondents’ practice has significantly positive correlation with attitude (r=.774 & p=.000). Similarly knowledge of the respondents positively correlated with practice significantly ( r=.765 & p=.000). So like attitude of the respondents is positively correlated with knowledge at statistically significant level. ( r=.891 and p= .000). There is a weak correlation of work experience with, attitude and practice where, r=.219 p=.009, r=176 p=.039 respectively. Knowledge was not correlated with year of experience.Conclusion: Research findings reported the strong correlation between knowledge attitude and practice, acknowledged a lack of full preparation in the EBP process to engage in and implement EBP consistently. Nurses working in the oncology setting should be provided the mentorship and support to obtain continuing education for better implementation of evidence based practice in their working institutions.